Dissociation of Object and Spatial Visual Processing Pathways in Human Extrastriate Cortex - Haxby, James V.; Grady, Cheryl L.; Horwitz, Barry; Ungerleider, Leslie G.; Mishkin, Mortimer; Carson, Richard E.; Herscovitch, Peter; Schapiro, Mark B.; Rapoport, Stanley I. (Proceedings of the National Academy of Sciences - PNAS, 1991)
The existence and neuroanatomical locations of separate extrastriate visual pathways for object recognition and spatial localization were investigated in healthy young men. Regional cerebral blood flow was measured by positron emission tomography and bolus injections of H2 15O, while subjects performed face matching, dot-location matching, or sensorimotor control tasks. Both visual matching tasks activated lateral occipital cortex. Face discrimination alone activated a region of occipitotemporal cortex that was anterior and inferior to the occipital area activated by both tasks. The spatial location task alone activated a region of lateral superior parietal cortex. Perisylvian and anterior temporal cortices were not activated by either task. These results demonstrated the existence of three functionally dissociable regions of human visual extrastriate cortex. The ventral and dorsal locations of the regions specialized for object recognition and spatial localization, respectively, suggest some homology between human and nonhuman primate extrastriate cortex, with displacement in human brain, possibly related to the evolution of phylogenetically newer cortical areas.